The Christian Origins of the Quranic Text: A Historical Investigation of Monk Bahira and Warakha son of Nofil’s influence on Muhammad (PBUH) - Muhammad Tayyab Usmani; Dr. Mumtaz Ahmad Salik (Al-Qamar, 2020)
This research article aims to assess the assumptions of orientalists and western academicians about Bahira or Bohaira as the origin, fundamental source of the Qur’anic text, and teacher of Prophet Muhammad (PBUH). According to their findings, Qur’an is not revealed by Allah but Muhammad (PBUH) was really the author of the Quran. They also affirm and claim that material in the Quran is composed in a Christian environment. Muhammad (PBUH) also taught biblical metaphysics from Bahira, Warakha son of Nofil, Abdullah son of Salam, Salman Persian, etc., who played such a larger role in the compilation of Muhammad’s Qur’anic text. According to Muslim scholarship and historical data, the Qur’anic text is revealed by Allah and Prophet Muhammad (PBUH) did not learn any single word from any human teacher. Assumptions of the Orientalists are being critically analyzed and also presented the opinions of those orientalists who are not ready to accept their meetings and borrowing materials, which played an important role in the formation and composition of the Qur’anic Text.